2021
DOI: 10.3389/fimmu.2021.627197
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Profile of Combining PD-1/PD-L1 Inhibitors and Thoracic Radiotherapy in Non-Small Cell Lung Cancer: A Systematic Review

Abstract: BackgroundThe combination of immune checkpoint inhibitors (ICIs) and thoracic radiotherapy (TRT) has shown significant clinical activity in patients with non-small cell lung cancer (NSCLC). However, the currently available data on adverse events (AEs) were derived from a small subset of patients included in prospective clinical trials or retrospective studies. Thus, we conducted this systematic review to determine the AEs associated with this combination treatment.MethodsAn electronic literature search was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 67 publications
(94 reference statements)
3
14
0
Order By: Relevance
“…In the era of immune therapy, ICI combined with TRT achieved striking survival benefits for both NSCLC and SCLC ( 5 7 ). As the most common high-grade and grade 5 adverse event ( 17 ), treatment-related pneumonitis deserves the uttermost attention in additive therapy of ICI and TRT. The incidences of any grade pneumonitis and G3+ pneumonitis in clinical trials of ICI after conventional TRT were 13-33% and 1-9%, respectively ( 6 9 ), whereas higher rates (56-62% and 2-14%, respectively) were observed in real-world data ( 11 , 18 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the era of immune therapy, ICI combined with TRT achieved striking survival benefits for both NSCLC and SCLC ( 5 7 ). As the most common high-grade and grade 5 adverse event ( 17 ), treatment-related pneumonitis deserves the uttermost attention in additive therapy of ICI and TRT. The incidences of any grade pneumonitis and G3+ pneumonitis in clinical trials of ICI after conventional TRT were 13-33% and 1-9%, respectively ( 6 9 ), whereas higher rates (56-62% and 2-14%, respectively) were observed in real-world data ( 11 , 18 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al. ( 58 ) thought that RT rather than ICIs might be the leading reason for the similar incidence of PD-1 and PD-L1 inhibitors when combined with RT. Thus, the selection of candidate ICIs is recommended, primarily depending on their efficacy rather than the toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of grades 1-2 and grades 3-4 pneumonia in this study were 34% and 10%, respectively, higher than the incidence of <1% and 3% in ORIENT-15. Li et al [ 36 ] conducted a meta-analysis of 11 prospective clinical trials (1113 cases) of thoracic radiotherapy combined with immunotherapy for NSCLC and found that the incidence of pneumonia of all grades was 23%, and that in grades 3-5 was 3.8%, which validated the safety of radioimmunotherapy. However, it should be noted that the incidence of radiation-immune-associated pneumonia in real-world studies is higher than in clinical studies.…”
Section: Discussionmentioning
confidence: 99%